SEARCH FOR AND IDENTIFICATION OF GRAVITON EXCHANGE EFFECTS IN DRELL-YAN PROCESS AT LARGE HADRON COLLIDER - Pankov, A. A.; Serenkova, I. A.; Tsytrinov, A. V. (Одеські астрономічні публікації, 2013)
New physics signatures arising from different sources may be confused when first observed at future colliders. Thus it is important to examine how various scenarios may be differentiated given the availability of only limited information. Here, we explore the capability of the Large Hadron Collider (LHC) to distinguish spin-2 Kaluza-Klein towers of gravitons exchange from other new physics effects which might be conveniently parametrized by the four-fermion contact interactions. We find that the LHC with planned energies and luminosities will be capable of discovering (and identifying) graviton exchange effects in the large extra dimensions with the cutoff parameter of order 4.6 - 9.4 TeV (3.6 - 6.0 TeV) depending on energy, luminosity and number of extra dimensions.